Stories Travelling Across Nations and Cultures - Cattrysse, Patrick (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractEuropean filmmakers have often stated that linguistic diversity presents the major obstacle for European movies to cross national and cultural borders successfully. Some have even tried to make us believe that it would suffice to produce a movie in English to guarantee its international success. This article suggests that the effective use of some specific rhetorical devices might play a more important role in enhancing the chances of filmic narratives to travel successfully across nations and cultures. A thorough comparative study of the presence or absence of these rhetorical features and the use of language, applied upon a specific corpus of European movies, could enlighten us on the relative importance of the respective parameters within the larger discussion of movies travelling across nations and cultures and various translation policies.